Pengaruh Penggunaan Media Audiovisual Dengan Pendekatan Metakognitif Berbasis Masalah Terhadap Hasil Belajar Fisika Siswa Kelas XI IPA Di SMAN 1 Gerung Tahun Pelajaran 2016/2017 - Lalu M. Eka Prayudi; Hairunnisyah Sahidu; Gunawan Gunawan (Department of Physics Education, Universitas Mataram, 2017)
The purpose of this study is to examine the effect of audiovisual media with problem based metacognitive approach toward physics learning result of XI IPA at SMAN 1. The type of the study is experimental by using pretest-post test control group design. The population are XI IPA 1st semester students is 299. The technique that used to collect the sample is cluster random sampling, XI IPA 3 students as experiment class and XI IPA 4 students as controll class and each consist of 34 students. The media that used as audiovisual is powerpoint. Instrument that used is multiple choices consist of 20 question. The learning result of experiment class students and control class each 70.15 and 61.85. ÃÂ score experiment class and control class obtained consecutively 12.5086 and 12.9889, ÃÂ score is 15, so that both of class distibuted normally. Fcount ÃÂ score obtained 1.00 < FtabelÃÂ is 1.77 so that both of sample class is homogen. The data result analysis by using T-test onÃÂ both class by significant 5% and Tcount ÃÂ obtained is 2.45 and Ttabel ÃÂ is 1.99 on db 66, it means that Ho rejected and Ha accepted, so that it can be concluded there is an efffect of using audio visual media with metacognitive based on problem toward physics learning result of XI IPA at SMAN 1 Gerung accademic year 2016/2017.